A la poursuite du patrimoine - Thierry Nicolas (EchoGéo)
Among the phenomena common to French overseas departments, the reproduction of memorial markers associated with slavery is certainly one of the most significant of the last decade. From the Atlantic Ocean to the Indian Ocean, there is the same desire to introduce a different perspective on the slave period and to include commemorative sites in the environment. However, these memory places can hardly obtain the status of heritage components. In a paradoxical way, the obstacles to their integration in the Heritage are not related to the symptoms of the resurgence of a secessionist ideology. In this paper we will prove that the real cause of this non-integration lies to the lack of historicity of such places.